An Improved Model for the Estimation of Solar Radiation from Satellite Data for Thailand - Janjai, Serm; Masiri, Itsara; Pattarapanitchai, Somjet; Laksanaboonsong, Jarungsaeng (Journal of the Institute of Engineering, 2012)
This paper presents an improved model for estimating surface solar radiation from satellite data for Thailand. Digital data from the visible channel of the GOES9 and MTSAT-1R satellites were used as the main input data of the model. This model accounted for the scattering of solar radiation by clouds, absorption of solar radiation by water vapour, ozone and gases and solar radiation depletion by aerosols. Additionally, the multiple reflections between the atmosphere and the ground in satellite band, which were ignored in the original model, were included in the improved model. For testing its validity, the model was employed to calculate monthly average daily global solar radiation at 38 solar monitoring stations in Thailand. It was found that the solar radiation calculated from the model and that obtained from the measurements were in good agreement, with a root mean square difference (RMSD) of 6.1% and mean bias difference (MBD) of 0.3%. The performance of the improved model was better than that of the original model. DOI: http://dx.doi.org/10.3126/jie.v8i3.5939 JIE 2011; 8(3): 130-139